Crisis of the system of own resources of the European Union and proposals for the future - Mocoroa, Isabel Vega (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
Achieving the objectives of the European Union requires an increasing number of ambitious policies that are limited principally by the financial instruments at the disposal of the European Union. In May 2006, as the result of an inter-institutional agreement, the Commission was invited to undertake a full, wide ranging budget review covering all aspects of EU spending and its resources and to submit a report on this subject during 2008 and 2009. The European Commission launched a vast consultation on the reform of the budget and organised a Conference on “Reforming the budget, changing Europe”, on the 12th November 2008 in Brussels. The review of the current system of own resources as a system of financing the budgetary instruments appears to be necessary in order to address the principal criticism made presently on the lack of transparency and simplicity of the system. Its financial autonomy is limited vis-à-vis the national Treasuries and there is a need to reform the current budgetary imbalance correction mechanism which led to tensions among Member States due to a narrow accounting approach. In this article, we try to bring solutions to the crises of the system of own resources. The progress in the financial autonomy of the EU will depend on the new proposals to improve the current system of own resources. According to the nature and the weight of the elements of the system of own resources, the financial autonomy of the EU should be broader or more restricted in relation to that of the Member States. We plan to adopt measures, in the medium term which have an impact on the cause of the analysed problems offering a solution through a change in the structure of the current system in order to restore the principle of the EU financial autonomy. We propose the introduction of new own resources in the system which should replace the current VAT resource and a reduction in the GNI resource. To this end, we have completed a numeric evaluation of the potential formulas, based both on a general valuation and on another one with restrictions, thus, the more solid candidates to make up part of the new system in the short time, the more solid candidates are modulated VAT, a tax on the climate change and the EU corporation income tax.
Keywords: autonomia; instrumenty finansowe; Unia Europejska; podatek dochodowy od osób prawnych; podatek VAT